Match performance profile of goalkeepers during the 2019 COPA America soccer championship - Kubayi, A.; Larkin, P. (Medicina dello Sport, 2020)
BACKGROUND: The aim of this study was to analyse match performance of goalkeepers (GKs) during the 2019 COPA America soccer championship. METHODS: A total of 28 match observations were analyzed using the InStat® tracking system. Descriptive statistics (i.e., means and standard deviations), effect size (ES) and an independent t-test were used to analyze the data. RESULTS: Results indicated that GKs covered a mean total distance of 4675 m (minimum =3262 m; maximum =6181 m) per match. GKs of teams that won significantly had higher averages than GKs of teams that lost on the following technical variables: shots saved (%) (85.48±21.59; P=0.001; ES=1.42) and hand passes (%) (100±1.00; P=0.04; ES=0.82). In contrast, GKs of teams that lost significantly had higher averages on opponent`s shots (11.79±4.00; P=0.03; ES=0.85) and passes (24.71±6.68; P=0.05; ES=0.77) than those of teams that won. CONCLUSIONS: The present observations have practical implications for designing training programs and in-game tactics for GKs.